Histological, functional and transcriptomic alterations in the juvenile hippocampus in a mouse model of thyroid hormone resistance. Issue 2 (15th April 2022) - Fang, Yingxin; Dang, Pingping; Liang, Yue; Zhao, Defa; Wang, Ranran; Xi, Yue; Zhang, Dan; Wang, Wei; Shan, Zhongyan; Teng, Weiping; Teng, Xiaochun
Abstract : Background: Proper thyroid hormone signaling via the TRα1 nuclear receptor is required for normal neurodevelopmental processes. The specific downstream mechanisms mediated by TRα1 that impact brain development remain to be investigated. Methods: In this study, the structure, function and transcriptome of hippocampal tissue in a mouse model expressing the first RTHα mutation discovered in a patient, THRA E403X, were analyzed. RNAscope was used to visualize the spatial and temporal expression of Thra1 mRNA in the hippocampus of WT mice, which is corresponding to THRA1 mRNA in humans. The morphological structure was analyzed by Nissl staining, and the synaptic transmission was analyzed on the basis of long-term potentiation. The Morris water maze test and the zero maze test were used to evaluate the behavior. RNA-seq and quantitative real-time PCR were used to analyze the differentially expressed genes (DEGs) of the hippocampal tissues in the mouse model expressing the Thra E403X mutation. Results: The juvenile mutant Thra E403X mice presented with delayed neuronal migration, disordered neuronal distribution, and decreased synaptic plasticity. A total of 754 DEGs, including 361 upregulated genes and 393 downregulated genes, were identified by RNA-seq. DEG-enriched Gene Ontology (GO) and KEGG pathways were associated with PI3K-Akt signaling, ECM−receptor interaction, neuroactive ligand−receptor interaction, and a range of immune-related pathways. 25 DEGs were validated by qPCR. Conclusions: The Thra E403X mutation results in histological and functional abnormalities, as well as transcriptomic alterations in the juvenile mouse hippocampus. This study of the Thra E403X mutant offers new insights into the biological cause of RTHα-associated neurological diseases.